Influence of surface roughness on cyclists' velocity choices. Issue 1 (24th March 2021) - Toljic, Marko; Brezina, Tadej; Emberger, Guenter
Abstract : The purpose of this paper is to examine the influence of different roadway surfaces' roughness on cyclists' velocity choices. Could surface roughness be efficiently used for designing velocity choices according to needs in different locations? First, a survey to identify environmental conditions' impact on cyclist velocity choices is employed. The main part analyses the speeds of 3750 cyclists, measured with a radar gun on seven different surfaces: smooth and rough asphalt, painted cycle lanes, concrete, large and small cobblestones and gravel. By utilising a smartphone's built-in accelerometer affixed to a bicycle, the three-dimensional acceleration-based roughness of the surfaces is measured over a fixed distance. The analysis of scatter plots reveals that the vertical acceleration component approximates the total acceleration best. Ultimately, a numerical integration approach is used to derive comparable vertical distance values per surface type and fork stiffness. The collected data show that the 50th and 85th percentiles of cyclist speeds are similar on all surface types: 19·4–20·7 and 23–25·5 km/h. Furthermore, the data show only a weak correlation between measured velocity and surface roughness, thus suggesting that other, unconsidered factors outweigh the influence of the road surface and point the way to future research needs.